2003
DOI: 10.1016/j.ansens.2003.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The syntomic regulator for the K-theory of fields

Abstract: We define complexes analogous to Goncharov's complexes for the K-theory of discrete valuation rings of characteristic zero. Under suitable assumptions in K-theory, there is a map from the cohomology of those complexes to the K-theory of the ring. In case the ring is the localization of the ring of integers in a number field, there are no assumptions necessary. We compute the composition of our map to the K-theory with the syntomic regulator. The result can be described in terms of a p-adic polylogarithm. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In [5], two of the authors of the present work showed how one can sometimes compute the map reg p by using p-adic polylogarithms.…”
Section: The Theory Of P-adic L-functions Starts With Kubota and Leopmentioning
confidence: 99%
See 2 more Smart Citations
“…In [5], two of the authors of the present work showed how one can sometimes compute the map reg p by using p-adic polylogarithms.…”
Section: The Theory Of P-adic L-functions Starts With Kubota and Leopmentioning
confidence: 99%
“…Thus it provides a way of computing them, and Paul Buckingham wrote a computer implementation for this. In [5] Besser and de Jeu computed the syntomic regulator for (essentially) the part of the K-theory of a number field described by Zagier's conjecture and showed that it is given by applying the p-adic polylogarithm. Those p-adic polylogarithms were invented by Coleman [16] using his theory of p-adic integration but are not so easy to compute.…”
Section: The Theory Of P-adic L-functions Starts With Kubota and Leopmentioning
confidence: 99%
See 1 more Smart Citation
“…Formulas for the syntomic regulator are to be thought of as p-adic analogues of formulas for the Beilinson regulator [Bei85]. Several such formulas exists [Bes00c,BdJ03,BdJ04] for zero and one-dimensional varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of the complexes for F and C . Several parts of the constructions of the complexes in this section and in Section 2.5 below were carried out in earlier papers [de Jeu 1995;1996;Besser and de Jeu 2003], but we review them so that we can refer to the relevant details in some new constructions for ᏻ and in the calculations relating to regulators in later sections. Also, in various cases the constructions were carried out more generally, in which case they tend to become dependent on assumptions on weights in K-theory, and our exposition below will avoid such assumptions.…”
Section: 3mentioning
confidence: 99%